Effect of Cavity Design on the Strength of Direct Posterior Composite Restorations: An Empirical and FEM Analysis - V. Susila Anand; C. Kavitha; C. V. Subbarao (Hindawi Limited, 2011)
The aim of the present study was to verify the hypothesis that cavity design does not affect the strength of direct composite restorations as do material properties. Finite element modeling (FEM) and empirical testing were done for two cavity designs: a box shape (cube) and a concave shape (U). Two microhybrid composites were used to prepare the samples with the help of split stainless steel moulds. Compressive strength was tested. The results were statistically analyzed. Both FEA and empirical testing were complementary to each other in that the concave shape showed a significantly higher strength than box. Material properties affected the values only when box shape was used. The null hypothesis is thus rejected, and it is concluded that design significantly affects the strength of direct composite restorations.